Implementasi Kokurikuler dalam Menanamkan Nilai Edupreneurship Melalui Keripik Lumer di Kelas IV MIM Kauman Wiradesa - Salma Fitriani Novanda; Putri Nala Luthfiyah; Mariyatul Fadlilah; Fatimah Azzahra; Ferida Rahmawati (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This study aims to describe the implementation of co-curricular activities in instilling edupreneurship values through the production of “Keripik Lumer” (Melted Chips) among fourth-grade students at MIM Kauman Wiradesa. The activity was designed as contextual learning that emphasizes not only entrepreneurial skills but also Islamic values such as honesty, responsibility, and independence. This research employed a qualitative descriptive approach involving teachers and fourth-grade students as participants. Data were collected through observation, interviews, and documentation, then analyzed interactively using data reduction, presentation, and conclusion drawing. The results indicate that the co-curricular activity was implemented in a planned, systematic, and continuous manner through three stages: planning, implementation, and evaluation. The teacher acted as a facilitator who guided students to develop responsibility, teamwork, creativity, and motivation throughout the process. Students demonstrated high enthusiasm, independence, and discipline during the activities. Through direct experience, students not only understood entrepreneurial concepts but also internalized positive character traits such as cooperation, self-confidence, and perseverance. Therefore, co-curricular activities based on local products like “Keripik Lumer” proved effective as contextual learning media that foster an entrepreneurial spirit from an early age. This program can serve as an innovative learning model for the development of entrepreneurship education in elementary schools and madrasahs.